Senses of proximity in relations between Brazilian migrants mediated by smartphones: Senses of proximity in relations between Brazilian migrants mediated by smartphones (Simbiótica. Revista Eletrônica, 2024)
The article discusses the emotions and affections of Brazilian men and women migrants living in European cities in relation to the practices of using their social media on digital platforms. It aims to understand the feelings, emotions and affections of being and being a connected migrant and their relationship with their family networks, friendships and with natives and other migrants. The method used was structured and semi-structured interviews.
Keywords: connected migrant; digital platforms; emotions; affections; digital technologies